2022
DOI: 10.2147/ccid.s345106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epidemic Characteristics and Related Pathogenic Factors of 2726 Cases of Pityriasis Alba

Abstract: To understand the distribution characteristics of onset time, onset age and gender of pityriasis alba (PA) patients in the dermatology clinic of our hospital and to further explore the pathogenesis of the disease to provide a scientific basis for the prevention and treatment of this disease. Patients and Methods: The clinical data of 2726 outpatients with PA diagnosed for the first time from January 2016 to December 2020 were collected and descriptively analyzed. Results:The number of patients with PA was less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For babies and teenagers, sun protection and moisture retention measures should be stepped up throughout the peak PA season. (14) Etiopathogenesis of PA: It has been shown that there is no infectious agent responsible for this illness; hence it is not spread (15) . Many people with PA also have a history of atopic dermatitis (AD), and atopic individuals are at a higher risk for developing PA, lending credence to the theory that atopy and post-inflammatory alterations are at the root of the disorder (16) .…”
Section: Epidemiology Of Pamentioning
confidence: 99%
“…For babies and teenagers, sun protection and moisture retention measures should be stepped up throughout the peak PA season. (14) Etiopathogenesis of PA: It has been shown that there is no infectious agent responsible for this illness; hence it is not spread (15) . Many people with PA also have a history of atopic dermatitis (AD), and atopic individuals are at a higher risk for developing PA, lending credence to the theory that atopy and post-inflammatory alterations are at the root of the disorder (16) .…”
Section: Epidemiology Of Pamentioning
confidence: 99%